The college handbook of creative writing - DeMaria, Robert (Unites States of America : Harcourt Brace College Publishers, 1995)
Throughout the book are examples of effective writing, a number of which appear in their entirety. At the end of each chapter are discussion, questions and writing exercises. In addition, there are several useful glossaries and reference list.
Chapter1. Theme -- Chapter2. Setting -- Chapter3. Characters -- Chapter4. Plot -- Chapter5. Point of view -- Chapter6. Tone and style -- Chapter7. Description -- Chapter8. Dialogue -- Chapter9. Thoughts -- Chapter10. Time -- Chapter11. Images and sounds -- Chapter12. The performance factor: Plays and film scripts -- Chapter13. Fundamentals of writing -- Chapter14. Writing as a career
Includes bibliographical references and index.
Keywords: CREATIVE WRITING